Microbiome and Microbiota Within Wineries: A Review - Cristina Aires; Rita Maioto; António Inês; Albino Alves Dias; Paula Rodrigues; Conceição Egas; Ana Sampaio (Microorganisms)
The main goal of this work is to review the winery’s microbiota, from the grape to the winery’s microbial niches (fermentation tanks, surfaces, air), and their risks to wine and human health. The impact of climate change on the winery microbiome and related challenges are also discussed. Microbial diversity in wineries depends on several factors, such as the grape variety and its ripeness, temperature, relative humidity and the diverse activities of the winemaking process. Winery surfaces and equipment allow the establishment of a microbial community that can impact wine quality, the health of winery workers and visitors and even wine consumers. In the context of climate change, changes in the sugar content, phenolic compounds and the profile of hexoses and amino acids are already evident. These changes interfere with the fermentation microbiota and the quality of the wines, which are more alcoholic and less acidic. Furthermore, periods of drought or heavy rain favor species associated with berry diseases, including some capable of producing mycotoxins or harmful biogenic amines. In order to understand the impact of these changes on microbial communities, the use of various techniques will be discussed, such as flow cytometry, fluorescence in situ hybridization (FISH), quantitative polymerase chain reaction (qPCR) and metagenomic methods.